Note on occurrence of Lutke’s halfbeak Hemiramphus lutkei Valenciennes, 1847 (Beloniformes: Hemiramphidae), along Odisha Coast - Mohanty, Swarup Ranjan; Seth, Jaya Kishor; Mohapatra, Anil; Mishra, Subhrendu Sekhar (Journal of Fisheries, 2020)
The paper reports occurrence of Lutke’s halfbeak Hemiramphus lutkei Valenciennes, 1847, for the first time from the coastal waters of Odisha coast, India. This report confirms the occurrence of this species form an extended geographical range along the east coast of India and will be helpful in further study of its biology, zoogeography and taxonomic status of the family Hemiramphidae.